P138 Improving anti-fungal stewardship and the management of chronic pulmonary aspergillosis through a complex lung infection MDT. (12th November 2019) - Browne, A; Wilkie, M; Waqar, A; Shaw, A; Hill, K; Rae, N; Chalmers, JD; Fardon, TC; Connell, DW
Abstract : Background: Complex fungal lung infections such as Chronic Pulmonary Aspergillosis (CPA) require expertise for diagnosis and management. This challenge is now made more urgent by the recent rise in resistance to triazole drugs by Aspergillus sp. To address this, we now manage these cases through a novel Complex Lung Infection MDT. In doing so, we aimed to improve the decision-making around CPA diagnosis and management, whilst improving anti-fungal/triazole stewardship. Methods: The core MDT comprised three respiratory physicians with an interest in complex lung infections, an infectious disease physician, and two pharmacists with a special interest in this area, alongside a microbiologist, and an immunologist. There were six meetings in the initial twelve-month period from April 2018 to April 2019. We have analysed our management of Complex Fungal Lung Infections through the MDT in this time, with a specific focus on diagnosis and anti-fungal stewardship. Results: Of the 32 new cases discussed at the MDT over the six meetings, 13 were classified as complex fungal lung infections, with detailed analysis of their disease stage recorded as: 1 Sub-Acute Invasive Aspergillosis (SAIA), 7 Chronic Pulmonary Aspergillosis, 2 CPA/SAIA overlap, 2 CPA/ABPA overlap, and 1 ABPA/complex bacterial infection overlap. The cohort was highly co-morbid: 69.2% of new cases had a co-morbidity which influenced management, or required pharmacist-guided management of drug interactions. 10 of the 13 patients were initially treated with triazole drugs (7 Itraconazole, 3 Voriconazole); subsequent re-discussion meant that 6 of the 10 had changes to therapy (1 stopping, with 5 changing triazole drug to voriconazole or posaconazole). Therapeutic drug monitoring (TDM) occurred in 9 of the 10 patients, with subsequent dose or formulation changes. Conclusions: Discussion of patients with suspected complex fungal lung disease at our MDT has allowed a refinement in diagnosis of Aspergillus- associated lung diseases, as well as improved stewardship of triazole drugs, including decisions not to treat, and better anticipation of drug interactions and use of TDM. This approach may help mitigate the expected and worrying rise in anti-fungal resistance amongst Aspergillus sp .